Correlation between Moberg Pick-Up test and sensation threshold test after median nerve reconstruction - Marcolino, Alexandre Marcio; Barbosa, Rafael Inacio; Souza, Daniela Neto Aguiar de; Rebelo, Rafaela de Barros; Delgado, Priscila Martins; Mazzer, Nilton; Elui, Valéria Meirelles Carril; Fonseca, Marisa de Cássia Registro (Acta Fisiátrica, 2012)
Functional assessment of sensitivity is essential to analyzing the status, recovery, and effectiveness of the treatment program for patients who have suffered losses due to physical and/or sensory disability after peripheral nerve injuries. Such losses of sensation lead to a significant loss of hand function. Objective: The purpose of the present study was to establish a correlation between functional and sensory threshold tests after a peripheral nerve lesion in the hand. Method: Fourteen men aged 18 to 40 years, who had bruises and cut injuries at the volar region of the wrist resulting in median nerve lesion, were selected for study. All the subjects were at least 1-year post-surgery. An esthesiometer SORRI® and a modified Moberg pick-up test were used. The test was divided into two phases, one with eyes open and the other with eyes closed. Also, the same test was performed by two different examiners. It was a “blinded” test that was performed three times, being repeated by the examiners according to a random sequence kept during the entire evaluation. Mean age and standard deviation were obtained during analysis in which Pearson’s coefficient was calculated and the non-parametric Mann-Whitney test was applied at 5% significance. Results: The mean age was 27.14 years with a standard deviation of 6.43 years, with the lesions being more frequently seen in men aged 21 to 30 years. Also, 64% of the cases involved lesion of the dominant hand. Pearson’s coefficient (r) regarding the correlation between sensory threshold test and Moberg pick-up test ranged from 0.5 to 0.7, which was statistically significant. Confidence intervals and p-values obtained from the Mann-Whitney test showed no statistically significant differences. Conclusion: One can conclude, therefore, that despite lacking standardized measures, the Moberg pick-up test correlated with the functional test. However, further studies are needed to support validation and reliability of the two methods.